1992
DOI: 10.1213/00000539-199205000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sevoflurane on Diaphragmatic Contractility in Dogs

Abstract: The effect of sevoflurane on diaphragmatic contractility was investigated in 12 anesthetized, mechanically ventilated dogs with the thorax opened. Animals were divided into two groups of six each: the sevoflurane and time control groups. We assessed contractility by the transdiaphragmatic pressure (Pdi) during supramaximal stimulation of the phrenic nerve at frequencies of 0.5, 10, 20, 50, and 100 Hz under quasiisometric conditions. The integrated electrical activity (Edi) of the crural and costal parts of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
2
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 0 publications
1
14
2
3
Order By: Relevance
“…It is reported that the P di value during a normal sniff is more than 58.84 mmHg in men and more than 51.49 mmHg in women [37]. In veterinary medicine, the effect of different drugs on diaphragmatic contractility has also been studied by measuring P di in a fatigued diaphragm [7], [8], [11], [13], [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the P di value during a normal sniff is more than 58.84 mmHg in men and more than 51.49 mmHg in women [37]. In veterinary medicine, the effect of different drugs on diaphragmatic contractility has also been studied by measuring P di in a fatigued diaphragm [7], [8], [11], [13], [14].…”
Section: Discussionmentioning
confidence: 99%
“…While enflurane depresses diaphragmatic function in a dose-dependent manner, halothane and isoflurane show little effect on it [7], [8], [11], [12] and sevoflurane has an intermediate effect [13], [14]. It has also been shown that halothane depresses P di and the electrical activity of the diaphragm in spontaneously breathing dogs [5].…”
Section: Introductionmentioning
confidence: 99%
“…A study in dogs during propofol anaesthesia [17] detected a fall in TwPdi of 10% to 20%. Volatile anaesthetic agents have also been found to reduce diaphragm contractility in some animal studies [18,19,20], but not all [21].…”
Section: Discussionmentioning
confidence: 99%
“…The favorable recovery profile associated with propofol offers advantages over traditional anesthetic and sedative medications in clinical situations (1). Like volatile anesthetics (halothane, enflurane, isoflurane, and sevoflurane) (2)(3)(4)(5), propofol decreases contractility in nonfatigued and fatigued diaphragm (6,7). No studies have been reported evaluating the recovery from reduced diaphragmatic contractility caused by propofol.…”
mentioning
confidence: 99%